2005
DOI: 10.1016/j.bbmt.2005.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Clinical Outcome, and Management of Virus-Induced Hemorrhagic Cystitis in Children and Adolescents after Allogeneic Hematopoietic Cell Transplantation

Abstract: We analyzed the incidence, etiology, risk factors, and clinical management of hemorrhagic cystitis (HC) in 102 children who underwent allogeneic stem cell transplantation: 28 from matched siblings, 57 from unrelated donors, and 17 from mismatched relatives. Conditioning regimens consisted of high-dose chemotherapy (n=83) or total body irradiation (n=19). In all children, urine and plasma were prospectively screened for human polyomavirus (HPV; BK virus [BKV] and JC virus [JCV]) or adenovirus (AdV) DNA with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
148
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(178 citation statements)
references
References 32 publications
16
148
1
2
Order By: Relevance
“…33,34 In the paediatric HSCT setting, other authors have suggested a link between HuPyV infection and HC: for example, Gorczynska et al found that 22 of 52 (42%) HSCT patients with HuPyV viruria (BK, 48, JC, 4) developed HC; while Leung et al found that 2 of 11 (18%) patients with quantifiable BK viruria had HC. 21,34,35 This prospective study gives further relevance to the role of BK virus infection for HC in paediatric HSCT. We found that 87.5 and 75% of post-HSCT HC patients were associated with BK positivity in urine and/or blood, respectively, and that BK infection was the only risk factor for the development of HC.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…33,34 In the paediatric HSCT setting, other authors have suggested a link between HuPyV infection and HC: for example, Gorczynska et al found that 22 of 52 (42%) HSCT patients with HuPyV viruria (BK, 48, JC, 4) developed HC; while Leung et al found that 2 of 11 (18%) patients with quantifiable BK viruria had HC. 21,34,35 This prospective study gives further relevance to the role of BK virus infection for HC in paediatric HSCT. We found that 87.5 and 75% of post-HSCT HC patients were associated with BK positivity in urine and/or blood, respectively, and that BK infection was the only risk factor for the development of HC.…”
Section: Discussionmentioning
confidence: 88%
“…25 The initial treatment of HC consisted of supportive measures (hyperhydration, forced diuresis and/or bladder irrigation). For patients with persistent bleeding, therapy with prostaglandins, GM-CSF and 1,26 cidofovir (CDV) 21,27 and hyperbaric oxygen therapy were used at the discretion of the transplant physician. 1 In patients with BK-related HC and no signs of active acute GVHD, a reduction or temporary withdrawal of immune suppression was tried.…”
Section: Hsct Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemorrhagic cystitis (HC) is recognized as a significant cause of morbidity and sometimes mortality in patients undergoing hematopoietic SCT (HSCT) [1][2][3] shows a clinical manifestation varying from microscopic hematuria to severe hemorrhage with obstructive renal failure. 4,5 Its reported incidence ranges from less than 10% to more than 70% due to the discrepancies in definition criteria and the types of transplant.…”
Section: Introductionmentioning
confidence: 99%
“…Routine therapy for HC is based on intensive supportive treatment with hyperhydration, constant bladder irrigation, pain management and red cell or platelet transfusions. 2,13 Encouraging results with antiviral agents have been published; however, there is no evident proof in a large number of patients and mainly improve clinical symptoms. [14][15][16][17] The use of formalin, alum, prostaglandin E1, estrogens, FVIIa, factor XIII, hyperbaric oxygen treatment, intravesicular sodium hyaluronate, recombinant human epidermal growth factor or recombinant human GM-CSF has been described, but their efficacy remains controversial.…”
Section: Introductionmentioning
confidence: 99%